Natural killer cell distribution and trafficking in human tissues - Ferlazzo, Guido; Carrega, Paolo (Frontiers in Immunology, 2012)
Few data are available regarding the recirculation of natural killer (NK) cells among human organs. Earlier studies have been often impaired by the use of markers then proved to be either not sufficiently specific for NK cells (e.g. CD57, CD56) or expressed only by subsets of NK cells (e.g. CD16). At the present, available data confirmed that human NK cells populate blood, lymphoid organs, lung, liver, uterus (during pregnancy) and gut. Several studies showed that NK cell homing appears to be subset-specific, as secondary lymphoid organs and probably several solid tissues are preferentially inhabited by CD56brightCD16neg/dull non-cytotoxic NK cells. Similar studies performed in the mouse model showed that lymph node and bone marrow are preferentially populated by CD11bdull NK cells while blood, spleen and lung by CD27dull NK cells. Therefore, an important topic to be addressed in the human system is the contribution of factors that regulate NK cell tissue homing and egress, such as chemotactic receptors or homeostatic mechanisms. Here, we review the current knowledge on NK cell distribution in peripheral tissues and, based on recent acquisitions, we propose our view regarding the recirculation of NK cells in the human body.